1999
DOI: 10.1046/j.1365-2958.1999.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

The B regulatory subunit of protein phosphatase 2A is required for completion of macroconidiation and other developmental processes in Neurospora crassa

Abstract: rgb-1, encoding the tentative B regulatory subunit of the type 2A Ser/Thr phosphatase in Neurospora crassa, was isolated from cDNA and genomic libraries. Based on analysis of cDNA and genomic clones, rgb-1 is 3387 nucleotides in length, contains seven putative introns and encodes a 461-amino-acid polypeptide. Intron I, which is 5' to the presumed translation initiation codon, contains a uORF encoding 34 amino acids. Intron VI undergoes alternative splicing. Inactivation of rgb-1 by the repeat-induced point (RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0
4

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 37 publications
3
36
0
4
Order By: Relevance
“…Because the catalytic subunits of PP1 and PP2A (encoded for by the ppp-1 and pph-1 genes, respectively) are essential for cell survival in Neurospora and other eukaryotes (Yatzkan and Yarden 1995;Zeke et al 2003), we used repeat-induced point mutation (RIP; Cambareri et al 1989) to obtain partially functional To examine whether these mutations led to the decrease of the phosphatase activity of PP1, phosphatase assay (see supplemental materials) was performed using extracts prepared from cultures grown in LL, a condition that the clock is not running. The 32 P-labeled phosphorylase a is used as the substrate of the assay in the presence or absence of inhibitor-2, a specific protein inhibitor for PP1 (Krebs and Fischer 1962;Yatzkan et al 1998;Cohen 2002).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the catalytic subunits of PP1 and PP2A (encoded for by the ppp-1 and pph-1 genes, respectively) are essential for cell survival in Neurospora and other eukaryotes (Yatzkan and Yarden 1995;Zeke et al 2003), we used repeat-induced point mutation (RIP; Cambareri et al 1989) to obtain partially functional To examine whether these mutations led to the decrease of the phosphatase activity of PP1, phosphatase assay (see supplemental materials) was performed using extracts prepared from cultures grown in LL, a condition that the clock is not running. The 32 P-labeled phosphorylase a is used as the substrate of the assay in the presence or absence of inhibitor-2, a specific protein inhibitor for PP1 (Krebs and Fischer 1962;Yatzkan et al 1998;Cohen 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Because the catalytic subunits of PP1 and PP2A (encoded for by the ppp-1 and pph-1 genes, respectively) are essential for cell survival in Neurospora and other eukaryotes (Yatzkan and Yarden 1995;Zeke et al 2003), we used repeat-induced point mutation (RIP; Cambareri et al 1989) to obtain partially functional mutants of these two genes. RIP introduces random, but exclusively G-C to A-T point mutations during sexual cycle.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A report by Yatzkan & Yarden (1999) has suggested a link between PP2A regulatory subunit rgb-1 and macroconidiation in N. crassa: inactivation of rgb-1 leads to a failure in the formation of mature macroconidia. In contrast, we observed that macroconidiation was activated in PP179 (Fig.…”
Section: Discussionmentioning
confidence: 99%